Comparison of Graft Uptake and Postoperative Hearing Results between Butterfly-Cartilage and Temporalis-Fascia Myringoplasty - Sah, Amiya K; Rayamajhi, Pabina; Bhattarai, Hari (Journal of Institute of Medicine Nepal, 2020)
Introduction Myringoplasty is one of the commonest surgeries done in Otology for chronic otitis media- mucosal type (COM-mucosal type). The objective of this study was to compare the graft uptake and post-operative hearing status between butterfly-cartilage and temporalis-fascia myringoplasty. Methods Patients of age ≥15 years with COM-mucosal type with dry, small to medium sized central perforation of pars tensa with clearly visible perforation margin were randomized into two groups of butterfly-cartilage myringoplasty and temporalis-fascia myringoplasty. Graft uptake and hearing results were assessed after six weeks and results were compared within and between the groups. Results Thirty-one patients in butterfly cartilage group and twenty-nine patients in temporalis fascia group were analysed. Graft uptake rate was 93.5% (29/31) in butterfly group and it was 86.2% (25/29) in temporalis fascia group with no statistically significant difference (p= 0.34) between the two groups. The mean pre and post-operative air bone gap in butterfly cartilage group were 20.65dB±8.35 dB; 12.86dB±7.39dB and that in the temporalis fascia group were 19.72±6.14dB, 13.16dB±6.26dB respectively. The difference of preoperative and postoperative hearing status, obtained within the two groups was statistically highly significant (p< 0.001). However, there was no statistically significant difference in hearing results between the two groups (p= 0.54). Conclusion The graft uptake rate and hearing results of butterfly-cartilage group and temporalis-fascia group were statistically significant within the group after myringoplasty but there was no statistically significant difference in between the two methods.